MED20 is essential for early embryogenesis and regulates NANOG expression. Issue 3 (March 2019) - Cui, Wei; Marcho, Chelsea; Wang, Yongsheng; Degani, Rinat; Golan, Morgane; Tremblay, Kimberly D; Rivera-Pérez, Jaime A; Mager, Jesse
Abstract : Mediator is an evolutionarily conserved multi-subunit complex, bridging transcriptional activators and repressors to the general RNA polymerase II (Pol II) initiation machinery. Though the Mediator complex is crucial for the transcription of almost all Pol II promoters in eukaryotic organisms, the phenotypes of individual Mediator subunit mutants are each distinct. Here, we report for the first time, the essential role of subunit MED20 in early mammalian embryo development. Although Med20 mutant mouse embryos exhibit normal morphology at E3.5 blastocyst stage, they cannot be recovered at early post-gastrulation stages. Outgrowth assays show that mutant blastocysts cannot hatch from the zona pellucida, indicating impaired blastocyst function. Assessments of cell death and cell lineage specification reveal that apoptosis, inner cell mass, trophectoderm and primitive endoderm markers are normal in mutant blastocysts. However, the epiblast marker NANOG is ectopically expressed in the trophectoderm of Med20 mutants, indicative of defects in trophoblast specification. These results suggest that MED20 specifically, and the Mediator complex in general, are essential for the earliest steps of mammalian development and cell lineage specification.